2020
DOI: 10.1016/j.annonc.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

ARCTIC: durvalumab with or without tremelimumab as third-line or later treatment of metastatic non-small-cell lung cancer

Abstract: Background: Many patients with metastatic non-small-cell lung cancer (mNSCLC) experience disease progression after firstand second-line treatment; more treatment options are required for these patients. ARCTIC, a phase III, randomized, open-label study, assessed durvalumab AE tremelimumab versus standard of care (SoC) as ! third-line treatment of mNSCLC. Patients and methods: ARCTIC comprised two independent sub-studies. Study A: 126 patients with !25% of tumor cells (TCs) expressing programmed cell death liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 34 publications
(30 reference statements)
0
79
2
3
Order By: Relevance
“…For the end points (patient‐level) analysis, PFS and OS data were extracted from identified trials of durvalumab monotherapy in NSCLC, head and neck squamous cell carcinoma (HNSCC), and bladder cancer. Source studies included the ATLANTIC trial (phase II, greater than or equal to second‐line), 18 ARCTIC (study A; phase III, greater than or equal to third‐line), 19 and study 1108 for NSCLC (phase I/II, greater than or equal to first‐line), 20 CONDOR (phase II, second‐line), 21 and HAWK (phase II, second‐line) 22 for HNSCC, and data from study 1108 for bladder cancer 23 . Similar analyses were used to investigate the correlation between RECIST‐based objective response (i.e., complete or partial response) and OS.…”
Section: Methodsmentioning
confidence: 99%
“…For the end points (patient‐level) analysis, PFS and OS data were extracted from identified trials of durvalumab monotherapy in NSCLC, head and neck squamous cell carcinoma (HNSCC), and bladder cancer. Source studies included the ATLANTIC trial (phase II, greater than or equal to second‐line), 18 ARCTIC (study A; phase III, greater than or equal to third‐line), 19 and study 1108 for NSCLC (phase I/II, greater than or equal to first‐line), 20 CONDOR (phase II, second‐line), 21 and HAWK (phase II, second‐line) 22 for HNSCC, and data from study 1108 for bladder cancer 23 . Similar analyses were used to investigate the correlation between RECIST‐based objective response (i.e., complete or partial response) and OS.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the combined inhibition of PD-L1 and CTLA4 has attracted much attention (30). D Planchard et al reported that combination immunotherapy of PD-L1 and CTLA4 considerably prolonged the OS in advanced refractory colorectal cancer (31).…”
Section: Ctla4 Was Highly Related To Other Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Median PFS was 3.9 months (95% CI, 2.8-5.0) with Durvalumab plus Tremelimumab vs 5.4 months (95% CI, 4.6-5.8) with chemotherapy (HR, 1.05; 99.5% CI, 0.72-1.53; P = 0.71). ARCTIC [27] is another clinical trial evaluating the combination of Durvalumab and Tremelimumab compared to SOC chemotherapy. The results of the two studies suggested that Durvalumab alone or in combination with Tremelimumab had clinically signi cant improvement in OS and PFS compared with SOC.…”
Section: Discussionmentioning
confidence: 99%